Komunikasi Interpersonal Waroeng Noesantara Dalam Upaya Memberikan Pelayanan Berkualitas Untuk Menjaga Loyalitas Pelanggan - Sumiyati, Sumiyati; Herleandhi, Fery; Supriadi, Supriadi (CommLine, 2023)
This study aims to determine interpersonal communication between the leadership and employees of Waroeng Noesantara to maintain customer loyalty because, with customer loyalty, the product will continue to be sold, and it is assumed that it can be recommended to other consumers to add new customers. The research method used is a descriptive method with a qualitative approach. Primary data collection was carried out by interviewing key CEO informants, manager on duty support informants, baristas and cashiers, social media administrators, baristas, and three customers, while secondary data collection was carried out by observation and literature study. Data analysis uses the Miles and Huberman analysis model, namely an interactive model with data reduction stages, data presentation, conclusions, and verification data. Testing the validity of the data using source triangulation and technique triangulation the results of the study show that interpersonal communication between leaders and employees is effective so that it has an impact on the ability to provide quality service to customers so that customer loyalty is maintained. Recommendations from researchers suggest that there is an increase in responsiveness in service at the cashier.